Instrument construct of student's discipline attitude: Validity and reliability - Prihatni, Yuli; Pardimin, Pardimin; Anggasari, Novia Dewi (Research and Social Study Institute, 2023)
This study aimed to determine how the teacher's assessment of student discipline attitudes has been done all this time. Knowing how to develop an instrument for assessing students 'disciplinary attitudes that is standard and feasible to use, including: (a) what indicators are appropriate to measure students' disciplinary attitudes. (b) how to develop indicators for assessing disciplinary attitudes into questionnaire items. (c) determine the validity and reliability of the student's disciplinary attitude assessment instrument. In the end, to find out the degree of discipline of senior high school students. This research is a research and development. The subjects in this study were 312 class XI students of SMA Negeri 1 Karangdowo. Data collection was carried out by distributing questionnaires. The data analysis used included Exploratory Factor Analysis, reliability analysis using Cronbach's Alpha, and descriptive analysis. The result showed (1) the assessment of disciplinary attitudes by the teacher had not used valid and reliable instruments. (2) the results of the development of the instrument obtain indicators of discipline attitude, which are divided into 3, namely: obeying the general rules of schools outside the teaching and learning activities, obeying the rules of teaching and learning, and attendance in class, and obeying the rules of the learning task. The construct validity test of 50 items was declared valid with a Cronbach's Alpha value of 0.898, which was divided into 15 factors. (3) the tendency of discipline attitude of class XI students of SMA Negeri 1 Karangdowo is in the medium category